Powers of commutators as products of squares - M. Akhavan-Malayeri (International Journal of Mathematics and Mathematical Sciences)
Let F be a free group and x,y be two distinct elements of a free generating set, then [x,y] n is not a product of two squares in F, and it is the product of three squares. We give a short combinatorial proof.